SWOT analysis of plant health clinics as perceived by plant doctors in Nepal - Adhikari, R. K.; Regmi, P. P.; Thapa, R. B; G.C., Y. D.; Boa, E. (Journal of the Institute of Agriculture and Animal Science, 2018)
This paper identified and examined the internal and external forces that enable or inhibit the performance of plant clinics in Nepal. The study used web-based online survey tool to collect primary information. Likert scaling and indexing techniques were used on data analysis. Pretested set of questionnaires were mailed to 209 plant doctors and the response rate was 54.54%. Being ninth country to initiate plant health clinics, Nepal is successful to adapt this novel approach into the existing extension system. It has increased access to plant health services by providing wide range of services at a place. However,limited understanding and only profit motive of local private agro-vet and input dealers has created some biased-understanding and un-trust with clinic organizers. This SWOT analysis clearly spells the scope of plant clinics to fulfill the gap between farmers need and existing services provided by public extension system. Journal of the Institute of Agriculture and Animal Science. Vol. 33-34, 2015, page: 137-146